Echocardiographic Evaluation of Postoperative Coaptation Geometry of Left AV Valve in Complete Atrioventricular Septal Defect. (December 2022) - Kinami, Hiroo; Morita, Kiyozo; Shinohara, Gen; Uno, Yoshimasa
Background: We sought to determine the difference in geometric parameters in the left atrioventricular valve (LAVV) postoperative complete atrioventricular septal defect (CAVSD) compared to the normal heart, and the correlation between geometric and functional parameters for detecting the mechanism of LAVV regurgitation (LAVVR) in CAVSD. Methods: LAVV geometric parameters based on complete and acceptable quality echocardiograms of 18 patients with repaired CAVSD compared with 17 normal controls. LAVVR severity was also quantified by indexed vena contracta (I-VC) (mm) and % jet area/left atrium area (% Jet/LA), and the correlation with LAVV parameters in the CAVSD group was investigated. Results: In the CAVSD group, the posterior closing angle (Pc) was nearly the same as the anterior closing angle (Ac), yet in the normal heart, the Pc angle was double the Ac angle. The anterior opening angle (Ao) and posterior-to-anterior leaflet diameter ratio (a/p) in the CAVSD group was also significantly smaller. The CAVSD group also had a shorter indexed coaptation length (I-CL) and indexed tenting height (I-TH). Displacement length (ΔD) differed completely between the CAVSD and Normal groups, and also showed a strong positive correlation to the functional parameters of LAVVR (% Jet/LA: r  = .70, P  = .02; I-VC: r  = .60, P  = .02). Conclusions: The parameters in this study were applicable to CAVSD AV valve coaptation characteristics. We introduced 2 novel measures that may provide important insights into the differences in geometry and performance of the LAVV in repaired CAVSD as compared to normal hearts.